Right beside you - Monroe, Mary (Dafina Books, Kensington Publishing Corp., 2019)
With a successful career, money in the bank, and a solid future, Felicia Hawkins has almost everything she ever wanted. But getting married is the one holiday wish she can<U+2019>t seem to get. And it<U+2019>s not helping that she<U+2019>s hopelessly in love with her co-worker, widower Richard Grimes. They have the perfect office partnership, and he<U+2019>s as supportive as he is kind. But Felicia doesn<U+2019>t want to wreck their friendship by letting him know how she really feels . . . Richard has his hands full juggling pre-Christmas work demands and raising two teen daughters. But he<U+2019>s not too busy to wish his relationship with Felicia could become much more. He<U+2019>s drawn to her calm spirit and determination, along with everything they surprisingly have in common. And just once he<U+2019>d like a chance this season to dare tell her the truth . . . But what Felicia and Richard get instead is a cascade of misunderstandings; messy, well-meaning matchmaking from family and friends, and a long-distance transfer Richard can<U+2019>t refuse. Finally, in the middle of one chaotic snow-struck day, it will take all their courage and compassion to risk opening their hearts to each other<U+2014>hopefully for many more holiday happily-ever-afters . . .